Working Time Mismatch and Subjective Well-Being - Drago, R; Wooden, M; Warren, D (My University, 2007)
This study uses nationally representative panel survey data for Australia to identify the role played by mismatches between hours actually worked and working time preferences in contributing to reported levels of job and life satisfaction. Three main conclusions emerge. First, it is not the number of hours worked that matters for subjective well-being, but working time mismatch. Second, overemployment is a more serious problem than is underemployment. Third, while the magnitude of the impact of overemployment may seem small in absolute terms, relative to other variables, such as disability, the effect is quite large.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Employment -- Hours; Health -- Wellbeing; Employment; Health; Labour market; Health and wellbeing; Employment and unemployment; Health